2023
DOI: 10.1007/s00421-023-05184-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of long-lasting static stretching and hypertrophy training on maximal strength, muscle thickness and flexibility in the plantar flexors

Abstract: Maximal strength measured via maximal voluntary contraction is known as a key factor in competitive sports performance as well as injury risk reduction and rehabilitation. Maximal strength and hypertrophy are commonly trained by performing resistance training programs. However, literature shows that long-term, long-lasting static stretching interventions can also produce significant improvements in maximal voluntary contraction. The aim of this study is to compare increases in maximal voluntary contraction, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…According to Keiner et al (2022a) “strength plays a key role in jumping and sprinting performance, as athletes need to exert great forces within short time intervals during push-off and landing.” Since recent literature showed chronic stretching routines to be sufficient to enhance maximal strength ( Arntz et al, 2023 ) comparable with resistance training programs ( Warneke et al, 2023a ; Warneke et al, 2023b ), a positive influence of athletic performance was reasonably hypothesized. In some of the included studies, maximum strength increases were detected as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Keiner et al (2022a) “strength plays a key role in jumping and sprinting performance, as athletes need to exert great forces within short time intervals during push-off and landing.” Since recent literature showed chronic stretching routines to be sufficient to enhance maximal strength ( Arntz et al, 2023 ) comparable with resistance training programs ( Warneke et al, 2023a ; Warneke et al, 2023b ), a positive influence of athletic performance was reasonably hypothesized. In some of the included studies, maximum strength increases were detected as well.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, developing facility and time independent, safe, and effective training alternatives seem to be beneficial ( Morie et al, 2010 ; Schwendinger and Pocecco, 2020 ). Interestingly, recently published articles suggest high intensity ( Panidi et al, 2023 ) or high volume ( Arntz et al, 2023 ) static stretching can induce muscle hypertrophy and maximal strength increases, that were similar to resistance training adaptations, if performed appropriately ( Warneke et al, 2023b ). These results are in accordance with earlier research, indicating potential performance increases in response to chronic stretching routines ( Shrier, 2004 ; Medeiros and Lima, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…3 There are many traditional methods to treat calf muscle hypertrophy, such as selective neurectomy, total or partial gastrocnemius muscle resection, radiofrequency, and liposuction, but these procedures are associated with many complications, including irreversible loss of function, scarring, leg asymmetry, incision infection, and edema. 4 Liposuction is only used for fat hypertrophy. Because calf muscles have more fat, liposuction has little effect.…”
Section: Discussionmentioning
confidence: 99%
“…This study was performed to counteract methodological limitations described by Schoenfeld et al [ 22 ] and others [ 5 , 6 , 14 ], indicating that long stretching durations were impractical. While increasing strength may potentially be particularly relevant for sport-specific tasks such as jumping and sprinting [ 46 ], or ball throwing velocity in handball [ 47 ], a recently published systematic review did not find stretch-induced performance enhancement [ 48 ], which seems in accordance with the lack of results for the rate of force development and explosive strength parameters obtained in the current study [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Potentially using stretching as an alternative was suggested by Arntz et al [ 12 ] and Panidi et al [ 13 ] who reported that high-volume and/or high-intensity stretch training could potentially induce improvements in strength capacity. Accordingly, six weeks of one-hour daily self-administered calf muscle stretching induced increases in maximal strength, muscle thickness, and flexibility that were not significantly different from a commonly used resistance training routine (5 × 12 repetitions on 3 days per week for 6 weeks) [ 14 ]. Nevertheless, the plantar flexors can be considered a comparatively small muscle group with comparably low impact on multi-articular, complex (athletic) movements [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%